Anti-Bacillus and nitric oxide inhibitory activities of Malaysian Garcinia mangostana extracts and their major constituents - Karunakaran, Thiruventhan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Four types of crude extracts were obtained from the stem bark of Garcinia mangostana from which six xanthone derivatives: α-mangostin, β-mangostin, garcinone D, mangostenol, fuscaxanthone C and dulcisxanthone F were isolated. The structures of these compounds were elucidated and determined using spectroscopic techniques such as MS, 1D and 2D NMR. The in vitro anti-Bacillus assay was performed using the crude extracts as well as α-mangostin and β-mangostin against four Bacillus species; B. subtilis ATCC 6633, B. cereus ATCC 33019, B. megaterium ATCC 14581 and B. pumilus ATCC 14884. The ethyl acetate extract showed strong inhibitory activity against B. subtilis, B. cereus, B. megaterium and B. pumilus in disc diffusion assay with 10.33 ± 0.44 mm, 10.33 ± 0.44 mm, 9.00 ± 0.00 mm and 11.33 ± 0.17 mm inhibition zones, respectively. Nitric oxide inhibition activities indicated that two major compounds (α-mangostin, β-mangostin) exhibited very significant activity in the inhibition of LPS/IFN-γ stimulated RAW 264.7 macrophages with IC50 values of 29.81 ± 0.77 and 11.72 ± 1.16 μM, respectively. The chloroform and ethyl acetate extract of G. mangostana showed very potent activities.